The Effect of “Seiza” Sitting Position During Dzikr After Moslem Prayer on Stomach Circumference Changes: A Case Report - Muhammad, RakhaZidane; Kurniati, Amiroh; Budisulistyo, Trianggoro; Safitri, Nirmala (International Journal of Human and Health Sciences (IJHHS), 2023)
Introduction.The Japanese floor-sitting Seiza is reflected of femoral artery pinched, which improved of tissues oxygenation and circulation. It might play role on body metabolism, also the nerves system. Methods: Study was conducted on a 20-year-old obese man performed routinely dzikr with Seiza sitting, so the time duration counted. Stomach circumference and body weight was monitoring twice weekly until 1 month. Results: The stomach circumference measurements of 114 cm observed improvement, as at week 1 (1.75%), week 2 (0.88%), week 3 (63%), and week 4 (3.51%) underwent 316 to 334 seconds weekly of Seiza sittings. A 100,4 kg of body weight showed gradually improvement: 0.55%, 0.35%, 0.25%, and 1.89% in each weeks. Discussion: The Seiza sitting might be relate to St36 Meridian points. It stimulated of parasympathetic system, digest and absorption, aliementary glands activated, also fat metabolism. Conclusions: The Seiza sitting during dzikr after prayer might improve of body metabolism. International Journal of Human and Health Sciences Vol. 07 No. 02 Apr’23 Page: 202-206